First person - Edward Griffin (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Edward Griffin is first author on 'ApoE-associated modulation of neuroprotection from Aβ-mediated neurodegeneration in transgenic Caenorhabditis elegans', published in DMM. Edward conducted the research described in this article while a PhD student in the lab of Guy A. Caldwell and Kim A. Caldwell at The University of Alabama, Tuscaloosa, USA. He is now a postdoctoral fellow in the lab of David Standaert and Ashley Harms at CIRC 516, Birmingham, USA, investigating neurodegeneration, learning, memory and behavior.